2021
DOI: 10.1088/1748-9326/ac2fdd
|View full text |Cite
|
Sign up to set email alerts
|

Projected changes in global terrestrial near-surface wind speed in 1.5 °C–4.0 °C global warming levels

Abstract: Understanding future changes in global terrestrial near-surface wind speed (NSWS) in specific global warming level (GWL) is crucial for climate change adaption. Previous studies have projected the NSWS changes; however, the changes of NSWS with different GWLs have yet to be studied. In this paper, we employ the Max Planck Institute Earth System Model large ensembles to evaluate the contributions of different GWLs to the NSWS changes. The results show that the NSWS decreases over the Northern Hemisphere (NH) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…The state‐of‐art large ensembles (LEs) dataset from the Max Planck Institute Earth System Model (MPI‐ESM) is used to evaluate the effect of external forcing on the detected NSWS changes and the consistency of the results. The LEs dataset of MPI‐ESM includes 100‐member ensembles of simulations and has been evaluated by numerous studies (e.g., Refs 20, 31, and 32). The MPI‐ESM is a fully coupled atmosphere–ocean model, including land and ocean biogeochemistry processes, with a horizontal resolution of T63 (approximately 1.9° × 1.9°) and 47 vertical layers up to 0.01 hPa 32 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The state‐of‐art large ensembles (LEs) dataset from the Max Planck Institute Earth System Model (MPI‐ESM) is used to evaluate the effect of external forcing on the detected NSWS changes and the consistency of the results. The LEs dataset of MPI‐ESM includes 100‐member ensembles of simulations and has been evaluated by numerous studies (e.g., Refs 20, 31, and 32). The MPI‐ESM is a fully coupled atmosphere–ocean model, including land and ocean biogeochemistry processes, with a horizontal resolution of T63 (approximately 1.9° × 1.9°) and 47 vertical layers up to 0.01 hPa 32 .…”
Section: Methodsmentioning
confidence: 99%
“…Following Zha et al., 20 four latitude zones are defined as: area1 (60°N–90°N, 180°W–180°E), area2 (0–60°N, 180°W–180°E), area3 (45°S–90°S, 180°W–180°E), and area4 (0–45°S, 180°W–180°E). The SAT difference (SATD) is then calculated as follows: 0.28emSATDNHbadbreak=SATarea10.28emgoodbreak−0.28emSATarea20.28em$$\begin{equation}{\rm{\;}}SAT{D_{NH}} = SA{T_{area1}}\; -\; SA{T_{area2}}{\rm{\;}}\end{equation}$$ 0.28emSATDSHbadbreak=SATarea30.28emgoodbreak−0.28emSATarea4.$$\begin{equation}{\rm{\;}}SAT{D_{SH}} = SA{T_{area3}}\; - \; SA{T_{area4}}.\end{equation}$$…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could reduce dust emissions by driving an expansion of vegetation into arid regions 199 , although the magnitude of this effect is uncertain 200 . Terrestrial stilling, the observed downward trend in surface wind speeds over land surfaces 201 , could also affect dust emissions, with models suggesting a future reduction in Northern Hemisphere winds 202 . However, changes in atmospheric circulation patterns thought to impact surface wind speeds over dust producing regions may be more important 180 .…”
Section: Future Changes In Dust Radiative Forcingmentioning
confidence: 99%
“…From a global perspective, open-ocean and coastal winds are blowing harder in the Southern Hemisphere (Young and Ribal 2019) and in upwelling systems (Sydeman et al 2014), whereas terrestrial stilling (i.e., decline in surface winds until the 2010s; Roderick et al 2007) is expected to continue throughout the present century across mid-to-high latitudes of the Northern Hemisphere (Deng et al 2021;Zha et al 2021), despite of the reversal observed in the last decade (Zeng et al 2019). Among the possible causes discussed for the atmospheric stilling and reversal phenomena (Wu et al 2018), changes in land-use and surface roughness (Vautard et al 2010) and the internal decadal ocean-atmosphere oscillations ( most of these authors point out that a reinforcement in local circulations (i.e., sea-breeze, hereafter SB) could be driving these trends, as SB represent the dominant local wind in most coastal regions of the world (Simpson, 1994).…”
Section: Introductionmentioning
confidence: 99%